ChatGPT, the end of L2 academic writing or a blessing in disguise? - Hadizadeh, Abbas (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2024)
This paper provides an overview of the challenges and opportunities presented by ChatGPT and other AI-based technologies for writing skills, particularly academic writing in English as a second language. The paper includes a descriptive account of my interview with ChatGPT regarding the opportunities that it has presented and the challenges posed for L2 students and teachers. In addition, the paper offers some practical activities that can be implemented in L2 academic writing classes.